A priority oriented nutrition education program to improve nutritional and cardiometabolic status in the workplace: a randomized field trial - Bahar Hassani; Reza Amani; Mohammad Hussein Haghighizadeh; Marzieh Araban (Journal of Occupational Medicine and Toxicology, 2020)
Abstract Background Workplace nutrition has been identified as a priority setting that can significantly reduce cardiovascular diseases (CVD) risk factors. This study was conducted as a part of the workplace education program to improve nutritional practices and cardiometabolic status in industrial personnel. Methods The present research was a randomized controlled field trial conducted on employees of a regional petrochemical company. The health-related priorities of the program were defined and addressed in the study in which 104 employees with dyslipidemia were randomly divided into two groups of education and control. Data were collected pre- and post-intervention, using valid and reliable multi-session questionnaires on demographic data, nutritional knowledge, and nutritional intake. Anthropometric measures, serum FBS, HbA1C, hs-CRP and homocysteine (Hcy) were assessed in both groups. In the education group, the nutrition program included five educational workshops about healthy nutrition and regular exercise along with educational messages over a 3-month period. The controls did not receive any education during the study. Results There were no statistically significant differences between the two groups regarding the baseline variables. The education group significantly improved their nutritional knowledge (p < 0.001), dietary intakes (p < 0.005), serum FBS (p < 0.001) and Hcy levels (p < 0.001) and anthropometric indices. Conclusion Workplace nutrition education programs can improve knowledge and reduce important CVD risk factors.